# If α, β are the zeros of the polynomial f(x) = x2 – p (x + 1) – c such that (α + 1) (β + 1) = 0, then c =A. 1B. 0C. – 1D. 2

Given

f(x) = x2 – p (x + 1) – c

α and β are the zeros

Then,

f(x) = x2 – p (x + 1) – c

= x2 – px – (p + c)

As

(α + 1)(β + 1) = αβ + α + β + 1

= – p – c + p + 1

= 1 – c

So, the value of c,

c = 1

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos  Champ Quiz |Revealing the relation Between Zero and Coefficients38 mins  Relation Between zeroes and Coefficients46 mins  Interactive Quiz - Geometrical Meaning of the Zeroes32 mins  Relationship between Zeroes and Coefficients-238 mins  Relationship between Zeroes and Coefficients-152 mins  Quiz - Division Algorithm38 mins  Interactive Quiz:Polynomials43 mins  Division Algorithm-130 mins  Relation b/w The Zeroes and Coefficients of Cubic Polynomials54 mins  Solving Imp. Qs. of Olympiad on Polynomials47 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses 